Walking Trajectory Optimization Algorithm For Robot Humanoid on Synthetic Grass - Riananda, Dimas Pristovani; Wijayanto, Ardik; Alasiry, Ali Husein; Khalilullah, A. Subhan (EMITTER International Journal of Engineering Technology, 2018)
Synthetic grass surface is a new rule in international robot soccer competition (RoboCup). The main issue in the development of the RoboCup competition today is about how to make a humanoid robot walk above the field of synthetic grass. Because of that, the humanoid robot needs a system that can be implemented into the walking algorithm. This paper describes how to maintain the stability of humanoid robot called EROS by using walking trajectory algorithm without a control system. The establishment of the walking trajectory system is combined with a process of landing optimization using deceleration and heel-strikes gait optimization. This system has been implemented into a humanoid robot with 52 cm of height and walking on synthetic grass with different speeds. By adding optimization, the robot walks more stable from 32% to 80% of stability. In the next research, the control system will be added to improve the stability.